Configuring integrated supply chain network stochastic strategic - Hamidreza Fallah Lajimi (مدیریت صنعتی, 2015)
This research provides an optimization tool for use by supply chain managers in the design and operation of manufacturing- distribution networks under uncertain demand conditions. The problem under consideration consists of determining the supply chain infrastructure; raw material purchases, shipments, and inventories; and finished product production quantities, inventories, and shipments needed to achieve maximum profit while fulfilling demand and minimizing profit variability and unsatisfied demand. This research presented a model to supply chain infrastructure design. In this research, a multi-period, multi objective mixed integer robust optimization formulation of the strategic model is presented to account for the probabilistic demand data. For this purpose, numerical examples are presented and solved by LINDO software.